A New Flavonol Diglycoside from Solenostemma arghel Leaves - N. Michael, Helana (Asian Journal of Chemistry, 2010)
Chemical investigations on the leaves of Solenostemma arghel[Del] Hayne resulted in the isolation and identification of the newnatural flavonol glycoside: kaempferol 3,4' -di-O-β-D-glucosidebeside its 3-glucuronide, 3-rutinoside, 7,4'-diglucoside and theaglycone kaempferol were characterized. Their structure was establishedon the basis of chromatographic analysis, chemical degradationand UV spectroscopy and confirmed by 1H_NMR analysis.